Cross‐section metal sample preparations for transmission electron microscopy by electro‐deposition and electropolishing. Issue 5 (20th March 2013) - Niu, Rongmei; Han, Ke
<x xml:space="preserve">Abstract</x> A cross‐section sample preparation technique is described for transmission electron microscopy studies of metallic materials. The technique uses jet electro‐polishing for the final perforation. Examples are provided of using this technique for copper‐support/copper‐films/copper‐support multilayer structures, grown by electro‐deposition. The samples prepared by our current technique are compared with the ones made by ion‐milling. The technique is also applicable to materials which are susceptible to ion beam and thermal damages. Microsc. Res. Tech. 76:476–480, 2013. © 2013 Wiley Periodicals, Inc.